A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia) - Chatterjee, Tapas; Dovgal, Igor; Pešić, Vladimir; Zawal, Andrzej (Zootaxa, 2018)
Based on published records and original data, a list of the epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites is presented. Altogether 13 suctorian and 10 peritrich species from hydrachnid and halacarid mites were listed. From this list, six suctorian and one peritrich species have been reported from halacarid mites, while four suctorian and four peritrich species were found on hydrachnid mites determined up to species level. The remaining specimens were determined upto the generic level. The halacarid and hydrachnid species do not share any suctorian and peritrich species and some of the ciliate species are specific to certain taxonomic groups of the hosts.The host specificity of both suctorian and peritrich ciliates, localization on the host body and environment are discussed. Some ciliate species specific to hydrachnid mites prefer lotic or lentic habitats. In most cases, both suctorian and peritrich ciliates prefer only marine or only fresh water bodies. It was also mentioned that both suctorian and peritrich ciliates have not distinct preferences in localization on their host body.